2012
DOI: 10.1002/ejic.201200723
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recognition of the Higher Alkali Fluoride Ion Pairs by a Class of Coordination‐Driven Non‐Ditopic Ligands

Abstract: A first non‐ditopic system for selective recognition and binding of the higher alkali fluorides (KF, RbF, and CsF) is reported. Specific ion‐pair recognition was achieved by using vasarenes, a new class of self‐assembled bowl‐shaped compounds that show specific affinity toward the ion pairs and display no affinity for either the “free” cation or the anion. Vasarenes precipitate the higher alkali fluorides from solution, thus showing promising potential in separation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The vasarene family consists of self-assembled, vase-shaped compounds and their analogues, which are prepared by a onepot reaction between cyclic vicinal polycarbonyl compounds and polyhydroxy aromatics (Na et al, 2005;Almog et al, 2009). The supramolecular behaviors of these structures have been an ongoing study in our group, particularly their intriguing feature of selective affinity towards ion-pairs of type M + F À , M being a large monovalent cation (Almog et al, 2012). A recent study has shown that the multiple oxygen-containing functional groups of these ligands (hemiketals, carbonyls and hydroxyls) play a key role in this supramolecular binding mechanism by forming dimeric entities via strong [O-H-O] À hydrogen-bonding (Bengiat et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The vasarene family consists of self-assembled, vase-shaped compounds and their analogues, which are prepared by a onepot reaction between cyclic vicinal polycarbonyl compounds and polyhydroxy aromatics (Na et al, 2005;Almog et al, 2009). The supramolecular behaviors of these structures have been an ongoing study in our group, particularly their intriguing feature of selective affinity towards ion-pairs of type M + F À , M being a large monovalent cation (Almog et al, 2012). A recent study has shown that the multiple oxygen-containing functional groups of these ligands (hemiketals, carbonyls and hydroxyls) play a key role in this supramolecular binding mechanism by forming dimeric entities via strong [O-H-O] À hydrogen-bonding (Bengiat et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%
“…As mentioned earlier, we suggest that the presence of residual AcOH results in a selective precipitation with AcO À rather ISSN 2056-9890 than F À in the final complex. Similar to the original vasarene complexes with CsF (Almog et al, 2012;Bengiat et al, 2016b,c), the Cs + ion is stabilized by several interactions with the oxygen-containing functional groups of the ligand: hydroxyl (O3), carbonyl (O4) and etheric (O5), as well as by the additional EtOH solvate molecule (O1E) and the acetate counter-ion (O1A) (Scheme, Fig. 2).…”
Section: Structural Commentarymentioning
confidence: 69%
“…The supramolecular reactions of ligands from the vasarene family with ion-pairs of type M + F À , provided M is a large monovalent cation, have been studied extensively by our group in the past years (Almog et al, 2009(Almog et al, , 2012Bengiat et al, 2016a,b,c). The prerequisite regarding the size of the cation rests in the key role of the fluoride ion in initiating the complex formation (Bengiat et al, 2016b), though the contribution of the F À ion to the stability of the complex once formed has yet to be explored.…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Analogous compounds are readily prepared by reacting ninhydrin with other polyhydroxy aromatics. [2][3][4] Previous work by our group 5 has revealed the special affinity of vasarene towards compounds of the type M + F − (MF), where M is a large monovalent cation. As a ligand, it was able to solubilize the fluoride salts in organic solvents as well as binding and precipitating them as ion-pair•vasarene adducts by a non-ditopic mechanism.…”
Section: Introductionmentioning
confidence: 99%